ANALISIS STRATEGI GURU DALAM MENERAPKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN GOOGLE EARTH PADA MATA PELAJARAN IPAS KELAS V SDN 2 LABUHAN LOMBOK - Wahyuni, Aulia; Lalu Sirajul Hadi; Ilham Handika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the highly abstract nature of concepts in Natural and Social Sciences (IPAS) subjects particularly the topic of earth's relief which resulted in low student engagement and conceptual understanding among elementary students. This research aimed to describe in depth the teacher's strategies in planning, implementing, and evaluating IPAS instruction by integrating the Problem-Based Learning (PBL) model assisted by Google Earth media in Grade V at SDN 2 Labuhan Lombok. A qualitative descriptive approach was employed in this study. The primary subject was the fifth grade class teacher selected through purposive sampling. Data collection techniques included structured observations, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman model comprising data reduction, data display, and conclusion drawing with data validity verified through triangulation. The results revealed that the teacher's strategy was executed systematically across three stages. In the planning stage, the teacher designed instructional modules aligning PBL syntax with Google Earth's 3D spatial visualization, selected contextual local environmental issues (such as local flooding phenomena), and prepared digital infrastructure. During implementation, the teacher presented authentic problems via interactive satellite imagery, managed structured task-oriented group activities, and provided scaffolding and peer tutoring to resolve digital navigation hurdles. In the evaluation stage, the teacher applied a comprehensive authentic assessment covering affective, psychomotor, and cognitive domains through performance observation sheets and student worksheet analysis